2021
DOI: 10.1080/21655979.2021.1950279
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of the miRNA–mRNA regulatory network in fetoplacental arterial endothelial cells of gestational diabetes mellitus

Abstract: Gestational diabetes mellitus (GDM) increases the risk of fetal heart malformations, though little is known about the mechanism of hyperglycemia-induced heart malformations. Thus, we aimed to reveal the global landscape of miRNAs and mRNAs in GDM-exposed fetoplacental arterial endothelial cells (dAECs) and establish regulatory networks for exploring the pathophysiological mechanism of fetal heart malformations in maternal hyperglycemia. Gene Expression Omnibus (GEO) datasets were used, and identification of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…In line with this, except for miR-210-3p that was downregulated, all of them were upregulated by current hypoxia in fpEC. The fact that miR-210-3p, as a classical hypoxamiR, was reduced after 72 h of hypoxia is surprising, and we can only speculate that the induction of miR-210-3p by hypoxia has-as well as the cellular adaption to hypoxia in general [44]-a shorter dynamic than the time interval investigated here. We aimed to mimic chronic moderate hypoxic episodes, and thus, upregulation of miR-210-3p may have occurred before angiomiR analysis at 72 h. Interestingly, in rats, a downregulation of miR-210-3p was shown to enhance the expression of DNA repair molecules [45].…”
Section: Discussioncontrasting
confidence: 58%
“…In line with this, except for miR-210-3p that was downregulated, all of them were upregulated by current hypoxia in fpEC. The fact that miR-210-3p, as a classical hypoxamiR, was reduced after 72 h of hypoxia is surprising, and we can only speculate that the induction of miR-210-3p by hypoxia has-as well as the cellular adaption to hypoxia in general [44]-a shorter dynamic than the time interval investigated here. We aimed to mimic chronic moderate hypoxic episodes, and thus, upregulation of miR-210-3p may have occurred before angiomiR analysis at 72 h. Interestingly, in rats, a downregulation of miR-210-3p was shown to enhance the expression of DNA repair molecules [45].…”
Section: Discussioncontrasting
confidence: 58%
“…The research then uncovered that miR-423-5p decrement could hinder insulin resistance and hepatic gluconeogenesis in GDM mice via suppressing biochemical index levels, enhancing insulin homeostasis, relieving pathological changes, and reducing the apoptosis rate of pancreatic cells. Overall, miRNA exerts pivotal effects on maternal hyperglycemia through the interaction with mRNA [ 38 ]. Comparatively, our study specifically investigated the mechanism of miR-423-5p on GDM progression.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women with diabetes show changes in miRNA expression compared with healthy pregnant women, and changes in miRNA expression are also observed in the fetus and placenta. [9][10][11] A recent study identified 316 miRNAs dysregulated in the hearts of mice with streptozotocin (STZ)-induced diabetes mellitus. 12 Compared with that of healthy pregnant women, the expression of miR-21 in the serum and placenta of patients with gestational diabetes mellitus (GDM) is reduced.…”
Section: Introductionmentioning
confidence: 99%